Análisis de la eficiencia productiva del cultivo de arroz (Oryza sativa) en el contexto del cambio climático, Ignacio Escudero-Sullana, 2018-2023 - Celi Bances, Karla (2024)
This research work presented as its main objective: Analyze the productive efficiency of rice (Oryza sativa) cultivation in the context of climate change, in the district of Ignacio Escudero-Sullana, 2018 to 2023. Which sought to contribute to the knowledge about climate change and its effect. in rice production, given that research on the subject is scarce. The study was of a basic application type, with a quantitative-qualitative approach, and a non-experimental design. For the analysis, the SENAMHI database and an interview with a farmer were used, in which data was collected regarding Production Costs, Soil Temperature and Precipitation. After analyzing these data, it was evident that precipitation and soil temperature have an inverse and direct relationship with rice production, respectively.